Popular Culture Phenomena in Suzanne Collins’s Novel ″The Hunger Games″ - Syahruni Junaid; Muhammad Ikhsan (UIN Alauddin Makassar, 2014)
Abstract The aim of this study is to analyze and to describe the popular culture phenomena in the novel. The writer used sociology of literature approach to express and explain popular culture phenomena in the novel, then finding the relation between the context of the novel and the social condition in current society. The instrument which is used by the writer was note taking. Along this instrument, the writer read the novel, then taking note cards to write the popular culture expression on the novel, after that the expression is written down the writer classified the phenomena of popular culture from the novel. In this study, the writer found four popular culture phenomena in the novel. They are reality show, science fiction aspects, human competition, and heroine. Reality show has indicators, such as on screen appearance, the power of people’s support, planned dramas, and great prize availability. Next, two aspects of science fiction are world destruction and extraordinary creatures. Human competition has characteristics, e.g. survival, strategy, alliance, and losing. Then, the indicators of heroine are heroism, courage, displaying strength, and claiming the right to authority. This study implicates to realize people how popular culture has contaminated life and implicitly formed the perspective in looking at the surroundings. Expectantly, this thesis can stimulate the students of English Literature to learn more about the influence of popular culture to the contemporary literary works.